A influência da mídia nas decisões do tribunal do júri - Lucas, João Paulo dos Santos (Universidade Federal Rural do Semi-Árido, 2018)
The press plays an essential role as a communicating agent, but as a manifestly cultural element it has also taken on the role of opinion maker, without being aware of the impact it can have. This discourse has been very solid when considering the context of crimes against life news, whose judgment falls within the jurisdiction of the jury. It is known that the Judgment Council is made up of lay people, from society, who are directly at the mercy of media sensationalism around some of the most emblematic cases, and it may be possible for jurors to be influenced and, consequently, In this context, the main objective of this study is to analyze the influence of the media in the decisions of the Jury. To do so, the research consists of a bibliographical survey, through which legal doctrine was sought, as well as in academic works of various natures, and in other types of reading, such as jurisprudence, journal articles and the like, to acquire subsidies for the purpose of elaborating concepts that contributed to the study's rationale. What the doctrine and critics have boringly pointed out is that media activity in the broad way as covers certain cases and without the presence of their due limits has caused serious imbalance in the criminal process, especially the individual subject to popular judgment that before even facing the process, ends up absorbing the presumption of guilt by virtue of the negative impact that the information is transmitted by the press.
Monografia
Keywords: Crime; Tribunal do júri; Sensacionalismo; Mídia; Crime; Jury court; Sensationalism; Media; CIENCIAS SOCIAIS APLICADAS::DIREITO